2021
DOI: 10.32332/joelt.v9i1.2687
|View full text |Cite
|
Sign up to set email alerts
|

Developing Interactive Learning Multimedia Based on Simulation Model

Abstract: The purpose of this research is to develop interactive multimedia namely Smile English that can be used as the media for learning reading especially for self-preparation on the Test of English for International Communication (TOEIC) material. This reading interactive media used a simulation model. This idea exploded after observing and collecting the data in the internal environment of Politeknik Negeri Batam Based on the placement test, it was found that about 540 (49,23%) of Polibatam students' test were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Multimedia combines various information elements such as text, graphics, images, photos, animation, and audio that clarify learning material (Damanik, 2020;Hidayati & Irmawati, 2019;Nugroho & Arrosyad, 2020). It is also supported by previous findings, which state that multimedia can display the objectives of learning (Lutfi et al, 2021;Siahaan et al, 2021;Wicaksono, 2016). Multimedia, used to make it easier for students to understand learning material to achieve specific learning goals, is often called learning multimedia.…”
Section: Discussionsupporting
confidence: 60%
“…Multimedia combines various information elements such as text, graphics, images, photos, animation, and audio that clarify learning material (Damanik, 2020;Hidayati & Irmawati, 2019;Nugroho & Arrosyad, 2020). It is also supported by previous findings, which state that multimedia can display the objectives of learning (Lutfi et al, 2021;Siahaan et al, 2021;Wicaksono, 2016). Multimedia, used to make it easier for students to understand learning material to achieve specific learning goals, is often called learning multimedia.…”
Section: Discussionsupporting
confidence: 60%
“…Media is used to support learning so that learning can run well. The media can also be interpreted as a link between the giver and recipient of information (Ayuni & Setiawati, 2019;Siahaan et al, 2021). Media use as a link between educators and students is learning (Aris et al, 2019;Wicaksono, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of students can be seen from how the Yuli Fajar Arifin / Website-Based Learning Media on Reading and Numeracy Content for Third Grade Elementary Schools results of the learning process that has been carried out during their education period. Learning media is one of the main ingredients in the learning process in schools (Aris et al, 2019;Siahaan et al, 2021). Student learning outcomes are determined based on the learning media used (Aris et al, 2019;Wicaksono, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The number of integrations of simulation model integrations with learning media as virtual laboratories (Arantes do Amaral & Hess, 2018;Siahaan et al, 2021) increased significantly during the pandemic. Various studies have identified the impact of using virtual facilitation for practical learning.…”
Section: Introductionmentioning
confidence: 99%